PERAN USAHA MIKRO KECIL DAN MENENGAH DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI KOTA PALANGKA RAYA - Ahmad Fauzi Nurhidayat; Egi Ispreidi Maha (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2023)
Economic activities have a significant impact on social wellbeing. By providing basic necessities like food and clothes, this welfare program demonstrates that the community is doing its best. Micro, small, and medium-sized enterprises (SMEs) may also make useful contributions toward this end. The role that UMKMs play in improving social well-being is the primary subject of this research. Using a library research technique and secondary sources, this study employs descriptive qualitative research methodologies. The economic section of this research found that the existence of micro, small, and medium firms (UMKM) considerably improved community wellbeing. When a country invests in its citizens, everyone benefits. It also offers a legal basis for the claim that some UMKM measures are intended to improve the quality of life for all members of the community.